Design of the biomedical calibration laboratory quality manual for EN 17025: 2005 - Doğu, Hande. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
According to the New Approach Directives, the CE Marking is obligatory for medical products: the manufacturer affixes this marking in order to be allowed to sell his product in the European market. CE marked devices can only be tested and controlled by accredited laboratories. It is the aim of this project to design the laboratory quality manual in compliance with the EN 17025 standard, for the Biomedical Calibration Laboratory of Boğaziçi University. By searching other related international standards, minimum documentation requirements are determined: besides a draft Laboratory Quality Manual, draft documents such as policies, procedures and instructions are prepared within the scope of this master thesis. In the Appendices, a simple strategy plan on how to implement the EN 17025 standard in BME Biomedical Calibration Laboratory is also presented.|Keywords: Laboratory Quality Manual, Accreditation, CE Mark, Biomedical Equipment
Keywords: Calibration -- Laboratory manuals.; Quality control -- Standards.; Biomedical materials.